2019
DOI: 10.1021/acs.orglett.9b00505
|View full text |Cite
|
Sign up to set email alerts
|

Direct Access to Alkylideneoxindoles via Axially Enantioselective Knoevenagel Condensation

Abstract: Contents  General S2 Screening of the reaction conditions S4 Determination of the absolute configuration S7 General procedure for the aEKC S14  Computational details S30 NMR traces S44  HPLC traces S69S2 General

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 67 publications
0
19
0
Order By: Relevance
“…In 1896, German scientist, E. Knoevenagel discovered that the condensation of aldehydes or ketones with compounds containing an active methylene group in the presence of bases, resulting in the formation of ethylene derivatives 43 , which is widely used in the organic synthesis and in the chemical˗pharmaceutical and perfume industries 55,56 . Generally, the Knoevenagel condensation were in moderate yields (30-95%) 57,58 . Here, we have found that Knoevenagel reaction of rhodanine with aldehydes (RA reaction) has very high efficiency (>98%) under mild conditions (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…In 1896, German scientist, E. Knoevenagel discovered that the condensation of aldehydes or ketones with compounds containing an active methylene group in the presence of bases, resulting in the formation of ethylene derivatives 43 , which is widely used in the organic synthesis and in the chemical˗pharmaceutical and perfume industries 55,56 . Generally, the Knoevenagel condensation were in moderate yields (30-95%) 57,58 . Here, we have found that Knoevenagel reaction of rhodanine with aldehydes (RA reaction) has very high efficiency (>98%) under mild conditions (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…63 Lin and Jin recently developed a diastereoselective epoxidation mediated by visible light. 64 Bencivenni was able to form axially enantioenriched 3-methylene oxindoles through a Knoevenagel condensation and, upon epoxidation, the high axially chiral enantioenrichment was maintained with a 5 : 1 dr. 65 The first report of an enantioselective epoxidation to form a spiro-epoxyoxindole was by Metzner and Briere in 2007, though only one example with 30% ee was given. 66 In 2011, Gasperi developed a moderately stereoselective epoxidation of 3-ylideneoxindoles using tert-butyl hydroperoxide with a prolinol catalyst.…”
Section: Spiroaziridinyl Oxindolesmentioning
confidence: 99%
“…Recently we focused our attention to the realization of organocatalytic desymmetrizations which enables the control of stereogenic axis using organic molecules as catalyst. Our target molecules were compounds bearing a C‐N stereogenic axis such as succinimides,, , C sp 3 –C sp 2 atropisomers and alkylidenecyclohexanes, where the axial chirality originates because of the locked rotation around a double bond, rather than for steric interaction with hindered substituents.…”
Section: Atroposelective Organocatalysismentioning
confidence: 99%
“…Focusing on the development of novel methodologies for the synthesis of axially chiral compounds, our attention was recently directed to the olefination reactions to produce alkylidenecyclohexanes,, which are, together with allenes, two “classical” examples of axially chiral compounds, fully stable at the stereogenic axis. The primary amine 9‐ epi ‐NH 2 ‐QDA ( 65 ) was used to promote the Knoevenagel reaction of oxindoles with 4‐substituted cycloexanones to yield enantioenriched cyclohexylidene oxindoles 71 (Scheme ) …”
Section: Atroposelective Organocatalysismentioning
confidence: 99%